2016
DOI: 10.1534/genetics.116.190389
|View full text |Cite
|
Sign up to set email alerts
|

Selection on Inversion Breakpoints Favors Proximity to Pairing Sensitive Sites in Drosophila melanogaster

Abstract: Chromosomal inversions are widespread among taxa, and have been implicated in a number of biological processes including adaptation, sex chromosome evolution, and segregation distortion. Consistent with selection favoring linkage between loci, it is well established that length is a selected trait of inversions. However, the factors that affect the distribution of inversion breakpoints remain poorly understood. "Sensitive sites" have been mapped on all euchromatic chromosome arms in Drosophila melanogaster, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 37 publications
(42 reference statements)
0
37
0
Order By: Relevance
“…Other possible mechanisms for inversions to directly generate variation in the population include setting up conditions for meiotic drive (Novitski, ) and disrupting synteny near “sensitive sites” (Corbett‐Detig, ). Although we recognize there a number of direct physical effects of inversion mutations that selection can potentially act on, here we conclude that breakpoint lesions have had minimal effects in generating phenotypic variation through the structural or expression alterations of boundary genes.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible mechanisms for inversions to directly generate variation in the population include setting up conditions for meiotic drive (Novitski, ) and disrupting synteny near “sensitive sites” (Corbett‐Detig, ). Although we recognize there a number of direct physical effects of inversion mutations that selection can potentially act on, here we conclude that breakpoint lesions have had minimal effects in generating phenotypic variation through the structural or expression alterations of boundary genes.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitive sites normally promote crossing over, however, an inversion can lead reduce levels of genetic exchange when near the sensitive sites. Corbett-Detig (2016) concluded this can lead to a selective advantage for the inversion. Here, we conclude that breakpoint lesions have had minimal effects in generating phenotypic variation through the structural or expression alterations of boundary genes for selection to act on, however, further studies that map D. pseudoobscura TADs in different arrangements, test for meiotic drive in heterozygotes, and map sensitive sites in D. pseudoobscura are needed to fully reject the position effect hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Certain cross over events could lead to chromatids that differ in length such that shorter chromatids are transmitted at higher frequencies. Finally, Corbett-Detig (2016) showed that large inversions are often in close proximity to “sensitive sites” in the D. melanogaster genome. Sensitive sites normally promote crossing over, however, an inversion can lead reduce levels of genetic exchange when near the sensitive sites.…”
Section: Discussionmentioning
confidence: 99%
“…In this case pericentric inversions that did not exhibit expected underdominance were those whose breakpoints disrupted "sensitive sites" necessary for normal crossing over (Coyne et al 1993). Interestingly, Corbett-Detig (2016) showed that breakpoints of cosmopolitan and recurrent paracentric inversions in D. melanogaster are closer to cytological bands containing sensitive sites than the breakpoints of rare inversions. This pattern was interpreted as evidence of positive selection for recombination suppression per se, but upon considering the crossover dependent fertility underdominance generated by overlapping paracentric inversions it would appear common cosmopolitan inversions' proximity to sensitive sites prevents them from suffering the effects of underdominance when heterozygous with another inversion.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of inversion breakpoints along a chromosome has been particularly informative, as these breakpoints exhibit several nonrandom patterns that have inspired models of inversion evolution (Federer et al 1967, Van Valen and Levins 1968, Krimbas and Powell 1992. One class of models explains the distribution of inversion breakpoints in terms of selection for inversion length or chromosomal placement and the resulting recombination suppression (Caceres et al 1997, Cáceres et al 1999, Corbett-Detig 2016. Alternately, inversion breakpoint patterns have been attributed to non-selective mechanisms by: 1) modeling the spontaneous mutational process as transposable element mediated, 2) using directionally biased spontaneous mutation rates, or 3) considering structural heterozygosity as autocatalytic, such that pairing difficulty at breakpoints causes chromosomal breakage and elevates rates of gene rearrangement (Novitski 1946, Bernstein and Goldschmidt 1961, Lim and Simmons 1994.…”
Section: Introductionmentioning
confidence: 99%